Thermal ecology of Galaxias platei (Pisces, Galaxiidae) in South Patagonia: perspectives under a climate change scenario - Barrantes, María Eugenia (2017)
The native freshwater fish Galaxias platei shows a wide latitudinal distribution in Patagonia, being found on both sides of the Andes. Currently, climate change poses one of the main threats to native fish, and its effects are appearing faster in high southern latitudes. The aim of this work was to analyse the possible effects of climate change in G. platei through its thermal responses. We hypothesized that juveniles of this species would be affected by indirect rather than by direct consequences of climate change. We determined the thermal tolerance polygon using Critical Thermal Methodology and preferred temperatures using a thermal gradient. Additionally, we evaluated routine metabolic rate using stop-flow respirometry. Results showed an intermediate to large polygon, with a non-negligible portion acquired through acclimation. Preferred temperatures and routine metabolic rates were positively related to acclimation temperature. Results suggest that G. platei thermal tolerance is dependent on its prior thermal history, have a eurythermal nature but maintain high levels of cold tolerance. Moreover, G. platei would be better suited at maintaining homeostasis at highest temperatures where more energy could be available for growth. This is the first time that thermal ecology data are registered for this species at its southernmost distribution.